Development of Internet communication and social networking in modern conditions: institutional and legal aspects - Chernysh, Roman (2020)
The development of the Internet, which has been active over the past two decades, is leading to the formation of new forms of human interaction on the World Wide Web. One of such forms is actually social networks, which from the beginning of their activity are used mainly as a way to ensure human communication. However, such a big number of consumers with the usual ways of buying goods and services, lead to the search for new platforms for companies to do business, which in turn provokes the transition of social networks to a fundamentally new level of activity.